Komunikasi Bencana Melalui Media Sosial sebagai Bentuk Informasi dan Edukasi kepada Masyarakat Kota Bengkulu - Dionni Ditya Perdana; Lisa Adhrianti; Dwi Aji Budiman (Universitas Multimedia Nusantara, 2022)
Bengkulu is an area that is prone to natural disasters in terms of its geographical condition. In addition, Bengkulu is currently facing non-natural disasters, one of which is the global COVID-19 pandemic. In dealing with disasters, it is necessary to have effective communication from the government to the community. With the current social restrictions, the use of media is one of the important things in communication. This study aims to analyze the communication carried out by the Bengkulu's Regional Disaster Relief Agency in an effort to provide disaster information and education to the community. In the study of Agenda Setting, the media has ability to show audiences the things that are important for them to pay attention. This study observes and analyzes the content shared by the Bengkulu's Regional Disaster Relief Agency on its social media pages (Facebook and Instagram). The research findings that the content displayed on the agency's social media is generally the form of reporting. The information shared is information when a disaster occurs, such as the magnitude of the earthquake and the number of COVID-19 cases. This information is not followed by pre- and post-disaster information. The content produced also does not open up space for interactivity to the audience. Other content is in the form of ceremonial activities. This shows that the Bengkulu's Regional Disaster Relief Agency has not made disaster education efforts through social media. The media agenda that is prepared only aims to show the performance of the agency to the public. Keywords: Bengkulu, Disasters Communication, Information and Education, Social Media